Исследование динамических параметров электропривода на базе двигателя с катящимся ротором - Кулинченко, Г.В.; Масленников, А.М.; Багута, В.А. (Електротехніка і електромеханіка, 2016)
Анализируются динамические параметры электропривода на базе двигателя с катящимся ротором. Точность позиционирования такого мехатронного модуля обеспечивается в результате исследования факторов, определяющих
электромеханическую и электромагнитную постоянные времени. Экспериментальная оценка времени переходного
процесса при управлении позиционированием модуля позволяет исследовать влияние различных параметров электропривода на его динамику Аналізуються динамічні параметри електроприводу на базі двигуна з ротором, що котиться. Точність позиціонування такого мехатронного модуля забезпечуються в результаті дослідження факторів, що визначають електромеханічну та електромагнітну сталі часу. Експериментальна оцінка часу перехідного процесу при керуванні позиціонуванням модуля дозволяє досліджувати вплив різних параметрів електроприводу на його динаміку. Purpose. Development and investigation of a dynamic model of
electric drive on the base of the rolling rotor motor (RRM) which
reflects the positioning of the actuator of the locking and
regulating equipment in time. Methodology. Analytical description of electromagnetic and mechanical processes in the electric
drive during the RRM shaft movement by using a system of differential equations. Numerical imitation modeling with the processes
visualization in the Matlab environment of the RRM rotor displacement with mechanical load in time. Results. It is shown that the
degree of influence of the value of the load inertia on the
dynamics of the object obtained by the waveform changes the
rotation angle of the rotor and motor speed in time. The degree
of influence of the value of the electromagnetic time constant of
the dynamics of the positioning of the actuator, and the nature
of transients during acceleration and fixing position of the rotor
with a predetermined moment of inertia for different values of
inductance. The effect of the ratio of electromechanical and
electromagnetic time constants of the nature of the transition
processes accompanying jog mode angular displacement of the
drive shaft on the base of RRM. Originality. The lack of technical
means to ensure acceptable accuracy time measurement of
angular displacement shaft of the actuator in jog mode offset by
using a laser meter which gives the opportunity to assess the
adequacy of the dynamic model of the RRM. Practical value. The
results of investigations allow to create a tool for optimization
of structural, technical and hardware and software solutions for
the improvement and modernization of the projected electric
locking and regulating equipment. The direction for improving
the dynamics of the drive on the basis of RRM is indicated
providing for an increase in its torque characteristics of the
motor by reducing the influence of the parameters of transients